Pemetaan Terhadap Penyebaran Unit Cabang Kantor Pos Di Kabupaten Wonogiri - Muhammad Hasbi; Didik Nugroho; Pamungkas Bayu Aji (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
The Post Office is one of the public facilities for the community because it serves service facilities in the form of postal services, package delivery, logistics and reliable financial services. However, the lack of information makes access to the location of post office services not informed of the location distribution. The purpose of this research is to create a mapping application for branch post office units to make it easier for the general public to get information about the nearest post office unit, using the K-Means Clustering Method. Users can choose which post office unit they want to choose based on their criteria. In functional testing (Blackbox) it was found that the system had been running according to the system design plan that had been made previously, while the validity test using the Silhouette Coefficient method showed the average value for cluster 1 was 0.282674, cluster 2 was 0.297377, and cluster 3 is 0.423516, which means the object is in a good or appropriate group because the Silhouette Coefficient value in each cluster is closer to 1, which means the better the grouping of data in one cluster.Keywords : K-Means Clustering, Post Office, Silhouette Coefficient